O processo de desenvolvimento de produto em empresas de base tecnológica: caracterização da gestão e proposta de modelo de referência - Mendes, Glauco Henrique de Sousa (Universidade Federal de São Carlos, 2008)
The new product development (NPD) is essential for the competitiveness, mainly for small and medium sized Technology-based Companies (TBCs), which innovation can be considered one of its main business process. The objective of this thesis is characterizing and proposing a reference model to the NPD in small and medium sized TBCs from the process control automation (PCA) and medical-hospital equipment (HME) sectors. The specifications to develop the reference model were done according to a practical research, which considered both quantitative and qualitative research method. Firstly, a survey was done based on a sample of 62 TBCs in order to characterize practices used in the NPD management. Elucidation of the results generated from the statistical procedures enabled to find a set of factors (practices) that affect the success of product development in these companies. Management factors related to the pre-development activities, the role played by the leader in the NPD project and the proficiency in executing the activities of technical development were indicated as a determinant factor of success. After this process, a qualitative research was done in four TBCs in order to analyse better the PDP of these companies. After the empirical evidence in the analysis and considering the theoretical reference about the NPD, it was possible to formalize a number of proposals which enabled a reference model to manage the NPD in small and medium sized TBC from PCA and HME sectors. The model has five dimensions: strategic orientation; process; organization and leadership, evaluation and performance and resources. The research enabled to characterize the NPD management in such a specific companies and to provide a reference model, which can be used as a diagnostic and support to the organization of the NPD management in small and medium sized TBCs.
Keywords: Processo de desenvolvimento de produtos; Empresas de base tecnológica; Setor de equipamentos médico-hospitalares; Controle de processo - automação; ENGENHARIAS::ENGENHARIA DE PRODUCAO